The Effect Of Using Magic Card As Media On The Ability Of Eighth Grade Students Of SMP Negeri 1 Siantar In Writing Descriptive Text - Damanik, Novry Yohanna; Siahaan, Sanggam; Nababan, Irene Adryani (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
This research aimed to investigate the effect of using Magic Card as media on the ability of eighth-grade students in writing descriptive text at SMP Negeri 1 Siantar. This study applied a quasi-experimental research design involving two groups, namely an experimental group and a control group. The experimental group was taught by using Magic Card media, while the control group was taught by using the conventional teaching method. The population of this research consisted of all eighth-grade students in the 2025/2026 academic year, and the sample was selected through purposive sampling. The sample consisted of 64 students divided into two classes: 32 students in the experimental group and 32 students in the control group. The instrument used in collecting the data was a writing test in the form of pre-test and post-test. The data were analyzed by using an independent sample t-test. The findings showed that the mean score of the experimental group improved from 55.25 in the pre-test to 71.69 in the post-test, while the control group showed only slight improvement. The result of hypothesis testing revealed that the value of t-observed was 7.29, which was higher than the value of t-table 2.000 at the significance level of 0.05. Therefore, the alternative hypothesis (Ha) was accepted. In conclusion, the use of Magic Card media significantly improved students’ ability in writing descriptive text. Magic Card media also created a more interactive, enjoyable, and motivating learning atmosphere during the teaching and learning process.